Here are two numbers: 384 and 128. There are two numbers that sum up to 384 and have a difference of 128. Let's call the greater one N 1 , 1 and the smaller one N 1 , 2 . There are two numbers that sum up to N 1 , 1 and have a difference of N 1 , 2 . Call the greater one N 2 , 1 and the smaller one N 2 , 2 . Continue defining this way until N 1 0 , 1 and N 1 0 , 2 . What is their product?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good job! This is exactly what I wanted.
The product of the inputs is 49152. Each pair of operations quarters the numbers. 4 5 4 9 1 5 2 = 4 8 .
The successive pairs are : (256,128); (192,64); (128,64); (96,32); (64,32); (48,16); (32,16); (24,8); (16,8); (12,4). Therefore the product of the numbers of the 10th pair is 48.
AH, no! This is way too complicated!
Log in to reply
Why?! The first of the 2n'th pair is 2 n 3 8 4 and the second is 2 n 1 2 8 . Here n = 5 .
So the 10'th pair is 2 5 3 8 4 , 2 5 1 2 8 or (12,4).
Log in to reply
Yeah, much better.
I thought you actually did it ten times. lol
Log in to reply
@Ruilin Wang – That list was given so that readers can get a clear picture.
From the introduction of the problem we can easily derive these formulas: N n , 1 = N n + 1 , 1 + N n + 1 , 2 N n , 2 = N n + 1 , 1 − N n + 1 , 2 Since this is true for any n it will also be true for n + 1 : N n + 1 , 1 = N n + 2 , 1 + N n + 2 , 2 N n + 1 , 2 = N n + 2 , 1 − N n + 2 , 2 Substituting these expressions in the first two equations and simplifying gives us: N n , 1 = 2 N n + 2 , 1 N n , 2 = 2 N n + 2 , 2 Which is still true for any n so: N 0 , 1 = 2 N 2 , 1 | N 2 , 1 = 2 N 4 , 1 | N 4 , 1 = 2 N 6 , 1 | . . . N 0 , 2 = 2 N 2 , 2 | N 2 , 2 = 2 N 4 , 2 | N 6 , 2 = 2 N 8 , 2 | . . . With N 0 , 1 = 3 8 4 and N 0 , 2 = 1 2 8 , to get N 1 0 , 1 and N 1 0 , 2 we need to substitute the expressions a total of four times into the initial equation, giving: N 0 , 1 = 3 8 4 = 2 5 ⋅ N 1 0 , 1 N 0 , 2 = 1 2 8 = 2 5 ⋅ N 1 0 , 2 And their product will be: N 1 0 , 1 ⋅ N 1 0 , 2 = 2 1 0 N 0 , 1 ⋅ N 0 , 2 = 2 1 0 3 8 4 ⋅ 1 2 8 = 2 1 0 4 8 ⋅ 2 3 ⋅ 2 7 = 4 8 In the end, we can find any N n , x number with these two pairs of formulas (one for odd number indexes, and the other for even number indexes): Even: N 0 , 1 = 2 n ⋅ N 2 n , 1 | N 0 , 2 = 2 n ⋅ N 2 n , 2 Odd: N 1 , 1 = 2 n ⋅ N 2 n + 1 , 1 | N 1 , 2 = 2 n ⋅ N 2 n + 1 , 2
Problem Loading...
Note Loading...
Set Loading...
We know that N 1 , 1 + N 1 , 2 = 3 8 4 and N 1 , 1 − N 1 , 2 = 1 2 8 Then we also have N 2 , 1 + N 2 , 2 = N 1 , 1 and N 2 , 1 − N 2 , 2 = N 1 , 2
Notice if we sub what N 1 , 1 and N 1 , 2 into our original equation we get that N 1 , 1 + N 1 , 2 = 2 N 2 , 1 and N 1 , 1 − N 1 , 2 = 2 N 2 , 2
We observe that each time we sub back once that variables in the previous equation are equal to twice the newly introduced ones, for example when we are four layers in we have N 4 , 1 + N 4 , 2 = N 3 , 1 and N 4 , 1 − N 4 , 2 = N 3 , 2
And so from the following equations N 3 , 1 + N 3 , 2 = N 2 , 1 and N 3 , 1 − N 3 , 2 = N 2 , 2 We get that 2 N 4 , 1 = N 2 , 1 and that 2 N 4 , 2 = N 2 , 2 so if we were at N 1 0 , x then we would get 5 doublings ending with the equations 2 5 N 1 0 , 1 = 3 8 4 and 2 5 N 1 0 , 2 = 1 2 8
Before we proceed we notice that 1 2 8 = 2 7 and 3 8 4 = 2 ( 1 9 2 ) = 2 2 ( 9 6 ) = 2 3 4 8 and so we determine that N 1 0 , 1 N 1 0 , 2 = 2 1 0 3 8 4 ⋅ 1 2 8 = 2 1 0 4 8 ⋅ 2 3 ⋅ 2 7 = 4 8